Rural Teachers' Perceptions of Support for Program Change - Earle E. Newton (Journal of Research in Rural Education, 1990)
This study was designed to examine the dynamics of change processes in a selected rural School juri iction over 5-year p rio with emphasis upon sources of support for teachers during early stages of the Implementation of multiple innovetions. According to teachers, changes adopted at the system level did reach th classroom. The most important sources of support for teachers included their own professional T?reparatlon, .extra effort, and aut0n.0 Y. Opportunities for inservice education were ranked high but organized orotessionet developm nt ctlvltle at the school level were relatively infrequent. When asked specificafly about support for multiple tnnovstions. teachers reported the most common forms of assistance to be the superintendent, related teaching materials, and discussion with other teachers